Metode Kepala Bernomor Struktur Pada Mata Pelajaran PAI di SMA Negeri 2 Aimas Kabupaten Sorong - Galela, Hayati; Siddik, Hasbi; Chudzaifah, Ibnu (Tarbiyah STAIN Sorong, 2018)
Islamic Religious Education is a conscious and planned effort in preparing students to recognize, understand, appreciate, believe, have noble virtues, practice Islamic teachings from the main sources of the Holy Qur'an and Al-Hadith, through guidance activities, teaching exercises, and use of experience. Based on observations at SMA Negeri 2 Aimas student learning outcomes in class XA is low at 38.46% low learning outcomes because in the learning process teachers still use lecture methods that make students bored. The purpose of this study was to improve student learning outcomes in class XA by applying the head numbered structure method. This research is a Classroom Action Research conducted at SMA Negiri 2 Aimas Sorong Regency which aims to improve student learning outcomes in Islamic Religious Education using the Numbered Head Structure method. The subjects of this study were class X A students of SMA Negeri 2 Aimas Sorong Regency in the odd semester of the 2015-2016 academic year totaling 13 people. This research was conducted in two cycles, namely Cycle 1 held 2 meetings and Cycle II held 2 meetings. Data retrieval is done using learning outcomes tests and observation sheets. Data about students 'analytical skills were analyzed qualitatively, while data about students' understanding of concepts were analyzed quantitatively using descriptive statistics descriptive statistical analysis with the SPSS 16.0 formula, for example, looking for average values. Islamic Religious Education learning outcomes for students of class X A of SMA Negeri 2 Aimas, Sorong Regency after applying the Numbered Head Structure method in cycle I students who completed 69.23% while in cycle II students who completed 84.61. In cycle, I the average value of learning outcomes of Islamic Religious Education was 71.00. In cycle II the average value of PAI learning outcomes is 86.31. In general the learning outcomes of Islamic Religious Education in class XA students of SMA Negeri 2 Aimas, Sorong Regency can be improved by using the Head Numbered Structure method. Thus the application of the Numbered Head Structure method can improve the learning outcomes of Islamic Religious Education (PAI) grade XA students of SMA Negeri 2 Aimas Sorong Regency.